The reality of professional education teachers in Jordan's use of modern learning strategies - Mohammad Omar AL-Momani; Elham Mahmoud Rababa (Inovasi Kurikulum, 2022)
The information revolution created today has created increased information and various learning resources. The existence of these developments causes teachers to need to re-identify how modern learning strategies and the application of teaching methods are primarily for teachers in vocational schools. This study was conducted to identify the reality of using modern learning strategies in teaching vocational education at the basic stage from the point of view of vocational education teachers in Jordan, where a descriptive analytical approach is used, and to achieve the objectives of the study and answers. In this study the method used is descriptive analytical method using a questionnaire as an instrument for research. Questionnaires were distributed online to research respondents who are teachers who teach in vocational schools. The results of the study found that the use of modern strategies in the educational process has a positive impact on students, in addition to the statistically significant differences between teachers who use modern learning strategies in teaching compared to teachers who apply traditional teaching methods. For further research, the authors recommend managing learning materials to facilitate and improve the implementation of active learning strategies. AbstrakRevolusi informasi yang tercipta pada zaman sekarang menciptakan meningkatnya informasi dan berbagai sumber belajar. Adanya perkembangan tersebut menyebabkan guru perlu untuk mengidentifikasi kembali bagaimana strategi pembelajaran modern dan penerapan metode ajar utamanya untuk guru pada sekolah kejuruan. Penelitian ini dilakukan untuk mengidentifikasi realitas penggunaan strategi pembelajaran modern dalam mengajar pendidikan kejuruan pada tahap dasar dari sudut pandang guru pendidikan kejuruan di Yordania, di mana pendekatan deskriptif analitis digunakan, dan untuk mencapai tujuan studi dan jawaban. Dalam penelitian ini metode yang digunakan adalah metode deskriptif analitik dengan menggunakan kuesioner sebagai instrumen untuk penelitian. Kuesioner disebarkan secara daring kepada responden penelitian yang merupakan guru yang mengajar di sekolah kejuruan. Hasil penelitian menemukan bahwa penggunaan strategi modern dalam proses pendidikan memberikan dampak positif bagi siswa, selain adanya perbedaan yang signifikan secara statistik antara guru yang menggunakan strategi pembelajaran modern dalam mengajar dibandingkan dengan guru yang menerapkan metode pengajaran tradisional. Untuk penelitian selanjutnya, penulis merekomendasikan untuk melakukan pengelolaan materi pembelajaran untuk mempermudah dan meningkatkan implementasi strategi pembelajaran aktif..Kata Kunci: Guru pendidikan kejuruan; kurikulum pendidikan; mata pelajaran pendidikan kejuruan; strategi pembelajaran; strategi pembelajaran modern